2013
DOI: 10.1002/jgrb.50291
|View full text |Cite
|
Sign up to set email alerts
|

Origin of two Verwey transitions in different generations of magnetite from the Chesapeake Bay impact structure, USA

Abstract: [1] We observed two different Verwey transition temperatures in fragments of crystalline basement rocks and impact sediments from the Chesapeake Bay impact structure, USA. Our study aims to the question if this feature can be used as shock indicator in impact craters. We distinguished three generations of magnetite. (1) Primary magnetite in crystalline basement rocks has average grain sizes up to several hundreds of micrometers and shows a regular T V at ≈ 121 K. (2) Shocked magnetite occurs in fragments of cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…In Reznik et al () we already suspected that the faint second T V at around 100 K (Figure ) might be related to some degree of distortion in the magnetite lattice. T V s around 100 K has also been observed in shocked magnetite from impacted rocks (e.g., Kontny & Grothaus, ; Mang & Kontny, ) and are suggested to indicate a small amount of vacancies and increased Fe 3+ concentration in surface layers of magnetite grains. The heated shocked 10, 20 and 30 GPa samples show an even stronger irreversibility below T V .…”
Section: Discussionmentioning
confidence: 75%
“…In Reznik et al () we already suspected that the faint second T V at around 100 K (Figure ) might be related to some degree of distortion in the magnetite lattice. T V s around 100 K has also been observed in shocked magnetite from impacted rocks (e.g., Kontny & Grothaus, ; Mang & Kontny, ) and are suggested to indicate a small amount of vacancies and increased Fe 3+ concentration in surface layers of magnetite grains. The heated shocked 10, 20 and 30 GPa samples show an even stronger irreversibility below T V .…”
Section: Discussionmentioning
confidence: 75%
“…Up to now, information on the correlation between magnetic susceptibility and shock‐induced microstructural and morphological changes in magnetite are rare. Mang and Kontny () report on impact‐related deformation features and magnetic susceptibility in magnetite from the Chesapeake Bay impact structure, USA. These authors showed a relationship between grain size of magnetite and the Verwey transition temperature measuring magnetic susceptibility as a function of low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This unique and specific interval will be referred as the "2 T v interval" in the following. Such observation is seldom reported in the literature (Liu et al, 2004;Carporzen et al, 2006;Mang and Kontny, 2013) and was interpreted so far as the magnetic signature of two populations with rather different distributions of grain sizes. The favored mechanism proposed for producing the two T v was a differential oxidation state, the smaller magnetite populations being more prone to oxidation than the larger one (e.g., Mang and Kontny, 2013).…”
Section: The Two Verwey Transitionsmentioning
confidence: 79%
“…Samples with two Verwey temperatures were reported in the Vredefort impact crater (South Africa) by Carporzen et al (2006 and and within the Chesapeake Bay impact structure, (USA) by Mang and Kontny (2013). The authors attributed the low temperature T v to a post impact population of magnetite with different stoechiometry that crystallized from melt pocket within planar deformation features and alteration halos during the impact event at 2.02 Ga. Vredefort is the oldest documented impact craters on Earth.…”
Section: Environmental Implicationsmentioning
confidence: 99%